Study of microwave imaging - Wang, Yu. (2011)
The report introduces the technology of Ground Based - Synthetic Aperture Radar (GB-SAR) Imaging, which can be very helpful when the optical sensors are blocked by the clouds or forest canopy. GB-SAR can monitor variable areas having an extension of a few square kilometers, at time intervals ranging from a few minutes up to several days. It uses relative motion between an antenna and its target region to provide typical long-term coherent-signal variations and defines the characteristics. In the report the program written in MATLAB is developed to present the 2-D images. Data required are signal spectrum, which are obtained by software and experiments. Besides, discussions are conducted to explore and verify the source of unpredicted bright spots on 2-D SAR Images with Ray Tracing Software. With locating antenna array designed perpendicular the along-track direction, the 2-D SAR Imaging is extended to 3-D GB-SAR experiment. All the parameters are reset to meet the needs of algorithm. Ideal data are generated to simulate the real experiment and 3-D SAR programs are developed to form the 3-D SAR image, which prove the feasibility of the experiment.